Count and mass across languages - Workshop on Count and Mass Nouns (2009 : University of Toronto); Massam, Diane (Oxford : Oxford University Press, 2012)
This volume explores the expression of the concepts count and mass in human language and probes the complex relation between seemingly incontrovertible aspects of meaning and their varied grammatical realizations across languages. The chapters in this volume explore the question of the cognitive and linguistic universality and variability of the concepts count and mass from philosophical, semantic, and morpho-syntactic points of view, touching also on issues in acquisition and processing.
Revised conference papers.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general -- Mass nouns -- Congresses; Grammar, Comparative and general -- Noun -- Congresses